2020
DOI: 10.1111/ajr.12613
|View full text |Cite
|
Sign up to set email alerts
|

Services for children with hearing loss in urban and rural Australia

Abstract: ObjectiveTo report satisfaction with services for children with hearing loss in urban and rural Australia.DesignMixed‐method approach using surveys and semi‐structured interviews.SettingAustralian organisations that serve children with hearing loss.ParticipantsOne hundred parents of children with hearing loss and 91 professionals that serve children with hearing loss completed surveys. Seven parents and eight professionals were interviewed.Main outcome measuresComparison of satisfaction with services in rural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The higher than expected postcodes identified for URTI, AT, and OM may be due to limited access to primary healthcare in these regions, as the majority of overlapping conditions were in regions outside of major towns. Several studies have reported on the increasing rates of hospitalisation for potentially preventable conditions with increasing distance from metropolitan regions, which may be due to limited primary health care services in outer regions [ 14 , 15 ]. However, some studies have found that the implementation of rural health clinics in regions lacking primary care services did not significantly reduce hospitalisations for potentially preventable conditions [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The higher than expected postcodes identified for URTI, AT, and OM may be due to limited access to primary healthcare in these regions, as the majority of overlapping conditions were in regions outside of major towns. Several studies have reported on the increasing rates of hospitalisation for potentially preventable conditions with increasing distance from metropolitan regions, which may be due to limited primary health care services in outer regions [ 14 , 15 ]. However, some studies have found that the implementation of rural health clinics in regions lacking primary care services did not significantly reduce hospitalisations for potentially preventable conditions [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, mothers reported being increasingly reliant on specialist services and health professionals based in metropolitan areas. Furthermore, this reliance causes its own issues as mothers experienced difficulty accessing support from the specialist services once back in their community as previously reported (Barr et al, 2020;Von Schuckmann et al, 2017). Specialist services need to encourage mothers to seek care locally and work collaboratively with rural clinicians in providing appropriate care and professional support.…”
Section: Discussionmentioning
confidence: 99%
“…In that, increasing geographical remoteness increases PPH due to limited primary health care services in outer regions. [14,15] However some studies have found that the implementation of rural health clinics in regions lacking primary care services did not signi cantly reduce hospitalisations for potentially preventable conditions. [16] This may be due to higher rates of multimorbidity experienced by some population groups in remote regions (in particular Medicare bene ciaries and those who identify as Indigenous), and the need for greater infrastructure and sta ng to provide more comprehensive services for those with complex needs.…”
Section: Main Ndingsmentioning
confidence: 99%